WEATHER CONDITIONS IN THE REPUBLIC OF ARMENIA CONNECTED WITH WEST-EUROPEAN ANTICYCLONE (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
The South-East crest of West-European anticyclone and the cold atmospheric front connected with it is one of the important synoptical processes for the formation of dangerous and unfavourable weather conditions in the territory of the Republic of Armenia. The analyses of synoptical and baric maps of the years 1948–2008 have shown that this type is repeated 4–5 times a year and is observed mainly during the months from October to April.
Keywords: West-European anticyclone; South-East crest; synoptical processes